2022
DOI: 10.5961/higheredusci.1085688
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Sürecinde Özel Gereksinimli Öğrenciler ile Çalışan Meslek Elemanlarının Gereksinimleri

Abstract: COVID-19 salgını nedeniyle birçok ülkede okulların kapatılmasıyla birlikte yüz yüze eğitime ara verilmiştir. Türkiye’de Millî Eğitim Bakanlığı 23 Mart 2020 tarihinde Eğitim Bilişim Ağı (EBA) üzerinden genel eğitime devam eden öğrenciler için uzaktan eğitim uygulamasını başlatırken, özel gereksinimli öğrencilere internet ortamındaki interaktif uygulamaları kullanmaları önerilmiştir. Bu nedenle özel gereksinimli öğrencilerin öğretmenlerinden aileleri bilgilendirmeleri ve öğrencileri sürece dâhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“… 19 The results of the studies in the literature showed parallelism with our study and showed that children with disabilities had difficulties in getting education during the pandemic process, could not benefit from distance education and mothers were not enough to provide education. 17 , 18 , 20 , 31 , 33 , 47 - 49 However, in some studies, it has been stated that mothers do not know how to get their children to do activities and it is important for mothers to be educated on this issue. 50 - 53 Another problem is that children with disabilities cannot benefit from distance education due to social inequalities, and there are studies supporting this result.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 19 The results of the studies in the literature showed parallelism with our study and showed that children with disabilities had difficulties in getting education during the pandemic process, could not benefit from distance education and mothers were not enough to provide education. 17 , 18 , 20 , 31 , 33 , 47 - 49 However, in some studies, it has been stated that mothers do not know how to get their children to do activities and it is important for mothers to be educated on this issue. 50 - 53 Another problem is that children with disabilities cannot benefit from distance education due to social inequalities, and there are studies supporting this result.…”
Section: Discussionmentioning
confidence: 99%
“…While it is important for children with disabilities to receive support from a specialist at home during the pandemic process, it has been reported that children cannot receive support from a specialist at home, similar to our study. 20 , 47 , 48 , 55 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations